THU0182 Waste Not, Want Not: Is Anti-TNF Wastage Preventable?. (23rd January 2014) - Bell, C.; Petford, S.; Tibbetts, L.-M.; Douglas, K. M.
Abstract : Background: Anti-TNF therapy (αTNF) has revolutionised rheumatology with undeniable improvements in patients' care, but also made it an expensive speciality. Humira, Enbrel and Infliximab are independently within the top 10 selling pharmaceutical products 2012 with combined estimated worldwide sales of 9.48, 8.37 and 7.67 billion respectively [1 ]. Financial accountability is imperative to modern medical practice and this includes minimising drug waste. In much of the UK injectable αTNF is delivered directly to patients' home, with financial benefits for NHS trusts, however any unused stock is wasted. Objectives: We aimed to quantify injectable αTNF waste, reasons for it and explore options for reduction. Methods: Patients return unused αTNF to the department as a drug safety measure. Patient details; volume of returned drug; and date are recorded on an Excel database. Returns between October 2011 and October 2012 were identified. Patients' clinical letters were reviewed to establish the timing, reason and a clinical decision made as to the predictability of drug discontinuation. A questionnaire was completed by clinical staff (7 Consultant, 3 SpR, 4 Clinical Nurse Specialist) regarding clinical scenarios of primary/ secondary failure and significant events requiring αTNF cessation. It explored knowledge of the process of stopping αTNF including its delivery. Results: In total 390 patients received injectable αTNF; 25 stopped (4 inefficacy, 12 side effects, 6 new contraindication, 3 other); 2 were deemed predictable. Conclusions: Annual un-used αTNF amounted to £35, 500 representing 1.4% of our departments £2.5million biologics spend. Whilst this is a small proportion, when dealing with large figures small percentages amount to considerable sums. Wastage was largely unpredictable; simply recognising patients expected to stop is thus unlikely to be beneficial. The questionnaire identified sources of unnecessary drug delivery due to delays in stopping αTNF. Clinical staff need education and a streamlined pathway for αTNF cessation instituted. Currently deliveries are made quarterly; reducing this interval would minimise waste without incurring extra cost to the Trust, but an increased workload preparing and dispensing prescriptions is inevitable. To uncouple any dissociation between decision making and prescribing 'flagging' prescription requests prior to assessment points (e.g. 6 months in RA) would ensure criteria are fulfilled and appropriate prescribing. We have identified local actions to reduce αTNF wastage. However, our experience is unlikely to be unique and consequently represents an area for considerable potential cost savings both within the UK and EU. References: FiercePharma 9 th October 2012 Disclosure of Interest: None Declared